PENGARUH METODE BERMAIN PERAN TERHADAP TINGKAT SELF AWARENESS PADA ANAK USIA 4-5 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Fardini, Indri; Chairilsyah, Daviq; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of the role playing methods towards the level of Self Awareness in children aged 4-5 year in Tk Islam Fatimah sub district Tampan of Pekanbaru City. The research used experimental method with one group pre-test post-test design. The sampel used in this study were 20 students. The data collection technique used is observation. Technique of data analysis using t-test by using program of Spss 25. Research hypothesis that there is the effect of the role playing method towards the level of Self Awareness of children aged 4-5 years in Tk Islam Fatimah sub district Tampan of Pekanbaru City. Based on data analysis known tcalculated = 14,567 > ttable = 2,145 with Sig. (2-tailed) = 0.000. Because Sig <0,05 it can be concluded that there are differences in levels of Self Awareness before and after the role playing method. It can be interpreted that there is the effect of the role playing method towards the level of Self Awareness of children aged 4-5 years in TK Islam Fatimah sub district Tampan of Pekanbaru City. Significant as much as 20,45%.Keyword: Level of Self Awareness, Role playing methods